La presenza dei valdesi nel territorio dauno - Caterina Celeste Berardi (Studia Paradyskie)
Waldism is the only so-called ‘heretical’ movement of medieval Europe to have survived until today, facing the threat of the inquisitorial repression implemented by the Church of Rome, continuously redefining its identity and becoming essentially a citizen of the origins (Lyon and the Lombard cities) to rural. In the Daunian territory the presence of the Waldensians has persisted for centuries up to the present day; the first appropriations, according to recent studies, presumably date back to the Angevin age (1266-1260). In this short contribution, three cities that today host Waldensian communities are examined in particular: Orsara di Puglia, Cerignola, Foggia, without forgetting the case of Monteleone of Puglia.